Agrotechnics and Medicinal Properties of Phacelia Tanacetifolia in Soil-Climate Conditions of Sirdaryo Region - Abdurashidova Malohat Abduqodir qizi (American Journal of Botany and Bioengineering, 2026)
Phacelia tanacetifolia is introduced into many countries due to its high ecological adaptability and economic benefits. However, its introduction into new territories may cause a number of ecological and agronomic problems. The rapid spread of the plant and aggressive growth in new territories may threaten ecological stability and lead to changes in regional flora and fauna. In addition, the adaptability of mountain phacelia to external conditions and its competition with alien plants pose a threat to some ecosystems. Therefore, before introducing the phacelia plant, it is necessary to carefully study its ecological impact and take the necessary measures. Scientific and practical research is needed to improve the action and efficiency of this plant.